Pendampingan Pemasaran Digital UMKM Jamu Warisan Nusantara Bude Wagiyem di Kota Bengkulu - Suci Mulya Utami; Mulyana Fathirnasari; Fakeri; Jaelani Muhammad Akbar; Nurrahmah Putry (LPPI UMN AL WASHLIYAH, 2026)
This community service activity aims to enhance the capacity of micro, small, and medium enterprises (MSMEs) in utilizing digital marketing to increase sales. The partner of this program is “Jamu Warisan Nusantara,” a traditional herbal MSME owned by Bude Wagiyem in Bengkulu City, which still has limitations in using digital platforms. The methods applied include observation, interviews, training, and direct assistance. The activities focus on creating business accounts, managing promotional content, and utilizing marketing features on social media platforms such as Instagram, TikTok, and WhatsApp Business. The results indicate an improvement in the partner’s understanding of digital marketing strategies, which has an impact on increasing consumer reach, promotional activities, and online orders. This assistance demonstrates that appropriate digital marketing strategies can improve the competitiveness of MSMEs, particularly those offering local wisdom-based herbal products made from Bengkulu’s traditional spices.